The Climate in Different Tourist Locations Affecting Children with Bronchial Asthma - Álvarez-Sánchez, Ana (2024)
Tourist destinations are chosen by travelers according to the characteristic climate of each place. These climatic changes, allergen variations, and air pollution contribute to trigger allergens that affect bronchial asthma symptoms. In addition, the increase in temperature and carbon dioxide levels in the atmosphere could lead to a more pronounced production of pollen, which leads to the spread of allergens, increasing sensitization and aggravating allergic reactions in children, especially in those who travel to tourist places such as mountains, beaches, hills, moors, among others. Due to the increasing emission of CO2 and other greenhouse gases, both in developed and developing countries, the negative effects on respiratory health, especially asthma and allergies, are becoming increasingly important, especially in young children and the elderly. Both global climate change and air pollution have a detrimental impact on respiratory health, especially in relation to asthma and various allergic diseases. Importantly, increased emissions of CO2 and various greenhouse gases contribute to climate change, resulting in more extreme and damaging weather events, such as periods of extreme heat, prolonged droughts, severe and devastating thunderstorms, floods, and powerful tropical storms. All these extreme weather events have negative consequences for people with asthma. As a result of the research, it could be corroborated that droughts cause an increase in the concentration of various allergens in the environment, such as pollen and outdoor fungi, which can cause allergic symptoms in sensitive people.